Etudes sur la Geographie du Canada - Grenier, Fernand (Book collections on Project MUSE., 2019)
The publication of the series, 'Studies in Canadian Geography, ' by the organizers of the 22nd International Geographical Congress, introduces to the international community of geographers a new perspective of the regional entities which form this vast countries. These studies should contribute to a better understanding among scholars, students, and the people of Canada of the geography of their land. Geographical works embracing the whole of Canada, few in number until recently, have become more numerous during the last few years. This series is original in its purpose of re-evaluating the regional geography of Canada. In the hope of discovering the dynamic trends and the processes responsible for them, the editors and authors of these volumes have sought to interpret the main characteristics and unique attributes of the various regions, rather than follow a strictly inventorial approach. In preparing this volume on Quebec, the contributors have looked at the evolution and present patterns of the ecumene of southern Quebec, rural and urban Quebec, and the dynamic biogeography of Quebec.